Stigma, Discrimination, and Well-Being Among California Adults Experiencing Mental Health Challenges - Wong, Eunice C. (RAND Corporation, 2015)
Presents results of the 2014 California Well-Being Survey, which tracks mental illness stigma and discrimination, well-being, and exposure to prevention and early intervention activities among Californians experiencing psychological distress.